Differences in human gene expression induced by tokishakuyakusan containing different grades of Angelica radix - Hayasaki, Tomoyuki; Kanaya, Shigehiko; Katoh, Akira; Ikeda, Tatsuhiko; Hanawa, Toshihiko; Sakurai, Masatomo; Oikawa, Tetsuro; Ninomiya, Yuka; Shojo, Masayuki (Journal of Traditional Medicines, 2010)
Pharmacological effects of two grades of Japanese Angelica radixes were compared by global transcriptional analysis in humans, and the differences were revealed by alterations in gene expression. An excellent-grade radix of Angelica acutiloba Kitagawa (Yamato-toki), produced in Nara, Japan, and a low-grade radix produced in China were dispensed to tokishakuyakusan formulation. These formulations were administered to separate groups of female participants for 4 weeks. Excellent-grade and low-grade Angelica radix were administered to 24 and 18 subjects, respectively. A global transcriptional dataset was obtained by cDNA microarray using RNA from peripheral blood nuclear cells of subjects. Partial least squares discriminant analysis and Student's t-test were combined to extract the transit data: (1) genes altered by the administration of both types of tokishakuyakusan and (2) genes altered by either type. Transients in (1) were categorized to have protein transport and transcription functions, with significance determined by the z-test for comparing two proportions. Transients in (2) were categorized to have translation, metabolic process, transcription, and ion transport functions. Results of (2) suggest that the difference exist in the protein level, metabolism, and cell regulation. Estrogen-related genes are included in the transcription category of (1), and neuronal-related genes are included in the metabolic process and ion transport categories of (2). These transitions may be related to the positive effect of each preparation in alleviating complaints.